Negative analysis: an application of negative theology for the analysis of poetry - Yurdaün, Nejat Cihan. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2007., 2007)
Negative theology is a branch of mysticism that is based on the conceptualization of God as an ultimate, transcendent and ineffable being. It creates its own language called Apophasis, which acting through a series of affirmations and negations, aims to approach the ineffable God. In a similar manner, poetry is a different language in language that aims to transcend the meaning capabilities of words in order to achieve purer relation with and through language. The unique experience the poet undergoes with language is also inexpressible in essence as every poet is a distinct being, and poet’s personal affiliation with language is singular. This study utilizes the concepts of negative theology in the analysis of poetry, grounding on this functional resemblance. The outcome is a method called negative analysis that works through diligent and close readings of poems. Negative analysis borrows concepts such as Apophasis, Cataphasis, negation, unknowing and inexpressibility from negative theology, and employs them in the analysis of poetry. Poems used in this study are G.M. Hopkins’ “Peace” and Emily Dickinson’s poem numbered 405 (It might be lonelier). In Hopkins, “silence” in its absence, and in Dickinson, “silence” in its presence, set the perfect ground to enable a study of these seemingly distinct disciplines, theology and literature, under a confluent gaze, with one method. This study aims to show that poetry is a special kind of language that demands a method of analysis befitting its special nature.
Keywords: Negative theology.